2006
DOI: 10.5694/j.1326-5377.2006.tb00482.x
|View full text |Cite
|
Sign up to set email alerts
|

The Threats to Australian Patient Safety (TAPS) study: incidence of reported errors in general practice

Abstract: Objective: To determine the incidence of errors anonymously reported by general practitioners in NSW. Design: The Threats to Australian Patient Safety (TAPS) study used anonymous reporting of errors by GPs via a secure web‐based questionnaire for 12 months from October 2003. Setting: General practices in NSW from three groupings: major urban centres (RRMA 1), large regional areas (RRMA 2–3), and rural and remote areas (RRMA 4–7). Participants: 84 GPs from a stratified random sample of the population of 4666 NS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 13 publications
2
49
0
2
Order By: Relevance
“…For example, a systematic review found that retrospective studies yielded a lower estimate of adverse drug events (3%),69 compared with prospective evaluations (10%) 70. Therefore, as with the overall rate of safety incidents, it is not possible to draw firm conclusions about the rate of consultations or people who experience diagnosis, communication or medication incidents, but we can say that these three broad categories made up the bulk of incidents recorded.…”
Section: Resultsmentioning
confidence: 99%
“…For example, a systematic review found that retrospective studies yielded a lower estimate of adverse drug events (3%),69 compared with prospective evaluations (10%) 70. Therefore, as with the overall rate of safety incidents, it is not possible to draw firm conclusions about the rate of consultations or people who experience diagnosis, communication or medication incidents, but we can say that these three broad categories made up the bulk of incidents recorded.…”
Section: Resultsmentioning
confidence: 99%
“…The reporting GPs demonstrated a clear understanding of the definition of error used 20. Investigators found less than 1% of reports to contain no safety event.…”
Section: Discussionmentioning
confidence: 97%
“…It has not been published in the peer-reviewed literature in full, however it can be viewed online 23. The TAPS electronic reporting system collects data of a similar nature to the additional axes and domains of ASIPS, including a harm scale, location check-box, event frequency scale, and details of patients such as age, gender and ethnicity 20. These elements are closed questions completed electronically by the reporter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one review of 15 studies, “errors” were estimated to happen in 1 in 120 patient consultations (0.8%), of which 60–83% were probably preventable 11. A recent Australian study in general practice found that the incidence of reported errors per patients seen per year was 0.24% 12. If we accept and extrapolate either figure, then with around 300 million patient consultations occurring in UK primary care annually,13 patient safety is potentially being compromised in a relatively large number of cases.…”
mentioning
confidence: 99%